THE EFFECT OF ALOIN ADMINISTRATION ON FOAM CELL FORMATION IN THE KIDNEYS OF MALE MICE (MUS MUSCULUS) WITH DYSLIPIDEMIA-INDUCED OBESITY - Nadya Mukhti; Ade Teti Vani; Khomeini Khomeini; Nadia Purnama Dewi; Dessy Abdullah; Rosmaini Rosmaini (Nusantara Hasana Journal, 2026)
Dyslipidemia and obesity are major metabolic disorders characterized by abnormal lipid metabolism, chronic inflammation, and oxidative stress, all of which contribute to progressive renal injury. Excessive accumulation of oxidized low-density lipoprotein (ox-LDL) promotes macrophage infiltration and foam cell formation within renal tissue, accelerating glomerular damage and increasing the risk of chronic kidney disease. Aloin, the principal anthraquinone glycoside isolated from Aloe vera, possesses potent antioxidant and anti-inflammatory properties that may attenuate oxidative injury and inhibit foam cell formation. This study aimed to investigate the effect of oral aloin administration on renal foam cell formation in male Mus musculus with dyslipidemia-induced obesity. A true experimental study employing a posttest-only control group design was conducted using male mice with experimentally induced dyslipidemia and obesity. Animals were randomly allocated into control and treatment groups. The treatment group received oral aloin for 28 consecutive days following dyslipidemia induction. Kidney tissues were collected for histopathological examination using Hematoxylin–Eosin staining. Foam cell formation was evaluated microscopically, and differences between groups were analyzed using the Independent Samples t-test with a significance level of p < 0.05. Histopathological analysis demonstrated that aloin administration reduced renal foam cell formation compared with the untreated control group. The treatment group exhibited approximately 25% foam cell formation, whereas the control group demonstrated approximately 93.8%. These findings suggest that aloin suppresses lipid accumulation and inflammatory responses within renal tissue through its antioxidant activity. Nevertheless, the therapeutic effect remained lower than that reported for atorvastatin, indicating that aloin is more appropriately considered a complementary rather than a replacement therapy. Oral administration of aloin effectively reduced foam cell formation in the kidneys of dyslipidemia-induced obese male mice. The protective effect is likely mediated through antioxidant activity, inhibition of lipid peroxidation, and attenuation of inflammatory processes.